Proceso de atención de enfermería para afrontamiento del estrés en pacientes hospitalizados. medicina interna. Hospital General Alfredo Noboa Montenegro Período abril - agosto 2024. - Dumbay Zaruma, Mishel Stefania (2024)
The hospitalization experience is a challenging period for patients, marked by anxiety and stress caused by an unfamiliar clinical environment and the loss of autonomy. This study aimed to determine a nursing care process for coping with stress in hospitalized patients in Internal Medicine, applying the Virginia Henderson model at Alfredo Noboa Montenegro General Hospital between October 2023 and February 2024. The methodology followed a quantitative approach with a descriptive and bibliographic scope, using a cross-sectional field design. Data were collected in the patients' natural environment to obtain a detailed understanding of their stress experience. The study population included 30 hospitalized patients who met specific inclusion criteria, focusing on those with at least two days of hospitalization who voluntarily participated in the study. The results revealed a notable prevalence of stress among patients, with most experiencing a moderate to severe level. This finding highlights the importance of addressing stress as a critical component of hospital care. Additionally, significant challenges were identified in meeting Virginia Henderson's 14 basic needs, such as breathing difficulties, elimination problems, pain while moving, and sleep disturbances, all of which negatively affect patients' quality of life and recovery process. Based on these findings, a nursing care plan was developed integrating NANDA, NIC, and NOC languages, effectively addressing the diagnoses. KEYWORDS: STRESS, HOSPITALIZED PATIENTS, NANDA, NIC, NOC, NURSING CARE PROCESS